The dual impact: physiological and psychological effects of rapid weight loss in wrestling - Sarıakçalı, Barış; Şahin, Fatma Neşe; Başoğlu, Burhan; Ceylan, Levent; Güler, Özkan; Yamak, Bade; Arıkan, Gökhan; Acar, Gizem Ceylan; Sekban, Gülşah; Durmuşoğlu, Mehmet Vakıf; Çimen Polat, Sezen; Küçük, Hamza (Frontiers in Psychology, 2025)
IntroductionAthletes competing in weight-class sports often seek to gain an advantage by competing at lower weights. Athletes competing in weight-class sports often seek to gain an advantage by competing at lower weights. To achieve this, they aim to lose weight during the competition period, leading to various physiological and psychological changes. This study aimed to investigate the biochemical, hormonal, and psychological effects of weight reduction in elite wrestlers during the competition phase.MethodsThirty-seven elite male free style wrestlers (age: 19.02 ± 1.27) participated in the study. Samples were collected 5 days before and on the day of the match.ResultsA significant decrease in body weight was observed (p < 0.05). Levels of creatine, BUN, sodium, hematocrit, hemoglobin, LDH, and cortisol increased, while albumin, testosterone, and FSH levels decreased. There were no significant differences in potassium, ALT, AST, TSH levels. State and trait anxiety scores of the wrestlers increased significantly during the RWL period.ConclusionThe study concluded that elite wrestlers experienced significant changes in physiological and psychological parameters during the competition periods. These findings underscore the importance of careful monitoring of RWL strategies by coaches and athletes to mitigate the adverse effects on nutritional status, psychological well-being, and physical performance.